JEPPE SINDING JENSEN A ANTROPOLOGICZNE DYSKUSJE WOKÓŁ RYTUAŁU. KU KONSTRUKTYWISTYCZNEJ REFLEKSJI NAD RYTUAŁEM RELIGIJNYM - Szafrański, Adam A. (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The Author tries to explain in anthropological discourse the transition from the “subject” language to the interpretative one. The former is present in functional and structural anthropology, the latter in the interpretative one. The former indicates mainly an integrative function of ritual, the latter a creative one. From the functional and interpretative point of view a ritual makes religion visible and reduces ritual to product of human activity. That reduction does not concern the phenomenological perspective.